A CRITICAL ASSESSMENT OF HEALTH BENEFITS OF CONSUMING ONIONS AND GARLIC: AN EMPIRICAL STUDY OF THE BENEFITS TO HUMAN HEALTH - ROSEMARY COLLINS PIATE, PH.D; USORO EKONG HARRISON (Scholar Express Journals, 2023)
The study aimed to analyze a critical assessment of the health benefits of consuming onions and garlic: an empirical study of their perceived effects on human health. Garlic and onion are among the oldest of all cultivated plants and are now used as food and for medical purposes. Onions, when combined with garlic, could have greater benefits. Together, the two are known to be effective antidepressants, painkillers, anticoagulants, and anti-inflammatory agents. For the purpose of increasing the level of resilience of onions, good preservative measures are needed. These will help reduce the perdition level during shipping and other areas of transit. The distribution of large quantities of onion bulbs has promoted large consumption of the products worldwide as they have been accommodated in many dishes, traditions, and cultures. Consequently, the study examined the concepts of onions, garlic, human health, the health benefits of consuming onions and garlic, the method of onion consumption, the method of garlic consumption, the adequate quantity of onions per day, and the adequate quantity of garlic per day. The study concludes that the health benefits of onions and garlic cannot be overemphasized. Even though it has not yet been acclaimed globally as a functional food, especially due to regulatory and legislative issues, the many health benefits of garlic have been documented. They are highly nutritious and have been associated with several benefits, including improved heart health, better blood sugar control, and increased bone density. One of the recommendations made was that there should be public enlightenment and awareness programs on the health benefits of garlic and onions, especially in work places, television, print media, and other avenues where such information could be transmitted to stimulate purchase decisions and ensure adequate use of them in foods.
Keywords: Health Benefits; Onions; Garlic and Human Health